White pages of biography of Marshal of the Soviet Union L. A. Govorov - A. V. Ganin (Омский научный вестник: Серия "Общество. История. Современность")
In the article, for the first time, previously unknown archival documents on the participation of the future Marshal of the Soviet Union L. A. Govorov in White movement in the East of Russia are being introduced into scientific circulation. The documents found from the funds of the Russian State Military Archive made it possible to establish that L. A. Govorov, after switching to the side of the Red Army in December 1919 concealed his service in the rank of second lieutenant on the orders of Admiral A. V. Kolchak in July 1919, the fact of voluntary admission to the service in the White Autumn of 1918 and other details of his combat path in the anti-Bolshevik camp